Bottom-up approaches and decentralized extension structures for improving access to and quality of extension services and technology adoption: Multi-level analysis from Malawi - Ragasa, Catherine; Alvarez-Mingote, Cristina; McNamara, Paul (Springer, 2024)
This paper looks at village agriculture committees, model villages, and stakeholder panels at various levels as participatory and decentralized structures for improving demand articulation and accountability in agricultural extension service provision in Malawi. It uses various datasets including nationally representative household and community surveys, a survey of service providers, a survey of representatives from the various structures, focus group discussions, and key informant interviews. It employs various estimation methods including matching techniques, matching plus regression adjustments, and an instrumental variables approach. Results show diverse experiences and functionality of these structures. Contrary to earlier reports, most of these structures are active, except for district stakeholder panels (DSPs), of which only about a quarter are active. Similarly, most of them provide a platform for discussion and feedback on service providers and the quality of their advice, except for DSPs. However, most structures were given poor ratings in terms of their responsiveness to the concerns and issues raised. Household participation in village development or agriculture committees is strongly associated with better household outcome indicators. These village committees, if they are active and responsive to farmers’ expressed concerns and needs, can contribute to better community-level outcomes. Results show that these village-level structures matter and that strengthening them is key to addressing their long-term functionality. On the other hand, a model village concept that focuses on an integrated approach to solving communities’ challenges is not associated with improved community outcome indicators; therefore, its implementation should be reviewed and improved to contribute to development outcomes.